2018
DOI: 10.17652/rpot/2018.3.14298
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Liderança Ética no Trabalho: Evidências de validade da versão brasileira

Abstract: bResumo O tema da ética nas organizações tem ganhado relevo recentemente. O objetivo deste trabalho foi realizar a adaptação da Escala de Liderança Ética no Trabalho (Kalshoven, Den Hartog, & De Hoogh, 2011). O primeiro estudo apresenta escala traduzida e o teste exploratório da estrutura fatorial com uma amostra de 222 profissionais. Apesar de apresentar 7 fatores (AFE), a estrutura encontrada não correspondente ao modelo original. No estudo 2 (amostra de 3804 profissionais), o ajuste do modelo com estrutura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…They also show that work engagement mediates the influence of abusive supervision on turnover intention. Therefore, if organizations are to minimize the risks of losing employees, they should invest in actions to select and train leaders, as well as in promoting an environment that strengthens values such as collaboration, consistency, transparency, respect and ethics (Almeida & Porto, 2019; Erickson et al. , 2015).…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…They also show that work engagement mediates the influence of abusive supervision on turnover intention. Therefore, if organizations are to minimize the risks of losing employees, they should invest in actions to select and train leaders, as well as in promoting an environment that strengthens values such as collaboration, consistency, transparency, respect and ethics (Almeida & Porto, 2019; Erickson et al. , 2015).…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…In the Brazilian context, however, studies focusing on this aspect of the supervisory relationship are still scarce, despite its potentially harmful consequences for organizations and especially for the subordinates themselves. A review of national literature [1] has shown only five empirical studies (Abelha, Cavazotte, Niemeyer & Villas Boas, 2020; Almeida, 2018; Almeida & Porto, 2019; Andrade, Aragão do Rosário, Moreira & Reis Neto, 2019; Ceribeli, Fernandes & Saraiva, 2021) in addition to a review of the international literature.…”
Section: Introductionmentioning
confidence: 99%
“…We administered the newly developed 37-item HLB questionnaire (see Table 4 for the items) to 218 employees (see Table 3 for sample details). Ethical leadership was assessed with 29 items from the Brazilian version (Almeida et al, 2018 ) of the Ethical Leadership at Work (ELW) scale (Kalshoven et al, 2011 ). An overall ethical leadership score was used.…”
Section: Measure Developmentmentioning
confidence: 99%
“…All items were evaluated using a Likert scale of 5 points, ranging from 1 (totally disagree) to 5 (totally agree). • Leadership: ethical leadership was evaluated using the 29-item Brazilian version of the Workplace Ethical and Leadership scale (Almeida, den Hartog, & Porto, 2018) proposed by Kalshoven et al (2011). This scale is composed of seven factors: People Orientation, Power Sharing, Fairness, Role Clarification, Integrity, Concern for Sustainability, and Ethical guidance.…”
Section: Methodsmentioning
confidence: 99%
“…The 20-item Abusive Leadership scale (Almeida, Den Hartog, & Porto, 2018) was used to measure abusive leadership behaviors. The scale used in this study measures four factors: Intimidation, Excessive pressure for results, Lack of care, and Self-centeredness.…”
Section: Methodsmentioning
confidence: 99%